2019
DOI: 10.1002/hep.30645
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐223 Ameliorates Nonalcoholic Steatohepatitis and Cancer by Targeting Multiple Inflammatory and Oncogenic Genes in Hepatocytes

Abstract: Nonalcoholic fatty liver disease (NAFLD) represents a spectrum of diseases ranging from simple steatosis to more severe forms of liver injury including nonalcoholic steatohepatitis (NASH), fibrosis, and hepatocellular carcinoma (HCC). In humans, only 20%-40% of patients with fatty liver progress to NASH, and mice fed a high-fat diet (HFD) develop fatty liver but are resistant to NASH development. To understand how simple steatosis progresses to NASH, we examined hepatic expression of anti-inflammatory microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 45 publications
5
102
0
Order By: Relevance
“…In addition, the decrease of miR-233 expression increased IL-6 and p47 phox expression in peripheral blood neutrophils from alcoholics 32 . It has been shown that miR-233 is a regulator of the progression of nonalcoholic steatohepatitis by targeting several inflammatory genes such as C-X-C motif chemokine 10 (CXCL10) and transcriptional co-activator with PDZ-binding motif (Taz) in hepatocytes 33 . The www.nature.com/scientificreports www.nature.com/scientificreports/ deregulation of miR-233, seen in our work, may be part of the pathogenesis of ACLF by macrophage polarization and alteration of cytokines involved in the inflammatory process.…”
Section: Variablesmentioning
confidence: 99%
“…In addition, the decrease of miR-233 expression increased IL-6 and p47 phox expression in peripheral blood neutrophils from alcoholics 32 . It has been shown that miR-233 is a regulator of the progression of nonalcoholic steatohepatitis by targeting several inflammatory genes such as C-X-C motif chemokine 10 (CXCL10) and transcriptional co-activator with PDZ-binding motif (Taz) in hepatocytes 33 . The www.nature.com/scientificreports www.nature.com/scientificreports/ deregulation of miR-233, seen in our work, may be part of the pathogenesis of ACLF by macrophage polarization and alteration of cytokines involved in the inflammatory process.…”
Section: Variablesmentioning
confidence: 99%
“…In line, half of miR-223KO animals developed HCC after long-term HFD feeding, showing an increased susceptibility to disease progression. Since miR-223 positively correlated with several chemokines (C-X-C motif chemokine 10, CXCL10) and cytokines (interleukin-6, IL-6) and with cancer-related genes (glypican 3, GPC3) in NASH patients, the authors hypothesized a protective role for miR-223 against malignant transformation and disease progression, contributing to the explanation as to why HFD feeding alone is not sufficient for NAFLD progression in mouse models [43]. These interesting findings depicting the anti-inflammatory role of miR-223 in NASH patients agree with data from other groups, as wee as our own, showing a downregulation of miR-223 in HCC with respect to surrounding nontumor tissues from surgically resected HCCs, corroborating the idea that high miR-223 levels restrain tumor development [3,44].…”
Section: Mir-223 Ko Mouse and Nafldmentioning
confidence: 99%
“…The data presented by Jimenez Calvente et al indicate that neutrophils could be a source of miR‐223 that is transmitted by microvesicles to shape macrophage phenotypes. However, this may possibly represent only a part of the full picture, because previous studies have claimed that monocytes and macrophages represent a potent source of miR‐223, and even epithelial cells from the liver (e.g., hepatocytes) might express miR‐223, or be the targets of immune‐cell–derived miR‐223 as well . Moreover, miR‐223 could also be transferred in a non‐membrane‐bound form associated with lipoproteins or Argonaut 2 (Ago2; Fig.…”
mentioning
confidence: 99%
“…Interestingly, miR‐223 was recently implicated in the pathogenesis of nonalcoholic steatohepatitis (NASH) and hepatocarcinogenesis. miR‐223 was found to be increased in mice with experimental steatohepatitis as well as in human NASH samples, whereas miR‐223‐deficient mice developed more severe steatohepatitis and liver cancer upon high‐fat‐diet feeding, suggesting that miR‐223 represents a key counter‐regulatory pathway for limiting disease progression . In fact, miR‐223 targeted inflammatory and tumorigenic genes in hepatocytes .…”
mentioning
confidence: 99%
See 1 more Smart Citation